the PEMBERDAYAAN REMAJA SEBAGAI KADER PENGAJAR AL-QUR'AN : (Studi Kasus di TPQ Darul Mukhlisin) - Arini, Aida; Ummam, Khoirul; Surur, Shobihus; Sa'diyah, Maidatus; Ridlwan, Burhanuddin; Said, Ali (ABIDUMASY, 2024)
Empowering teenagers as successor cadres of Al-Qur'an teachers at the Darul Mukhlisin Al-Qur'an Education Park (TPQ) is one of the strategic efforts to increase religious literacy among the younger generation. This program not only aims to teach the ability to read and write the Koran properly and correctly, but also to build character, leadership and social responsibility. This research examines the urgency of a cadre of Al-Qur'an teachers from youth elements and the impact of empowering teenagers as Al-Qur'an teachers, the challenges faced in its implementation, as well as the potential long-term benefits for individual teenagers, institutions and society. The method used in this research is Asset-Based Community Development (ABCD) method with discovery, dream, design, define, destiny.. The results of the research show that this empowerment program has a positive impact on teenagers in the form of awareness of potential and increasing the quality of literacy and leadership skills which have an impact on the social environment, by increasing religious motivation and understanding of Islamic values, which ultimately results in being able to practice knowledge by becoming a teacher of al- Qur'an at TPQ Darul Mukhlisin